Constructing Cerebellum Model by Researching on its Contributions to DIVA - Yuanyuan Wu; Shaobai Zhang (Institute of Advanced Engineering and Science, 2014)
DIVA (Directions into Velocities of Articulators) is a mathematical model of the processes behind speech acquisition and production, supposed to achieve a functional representation of areas in the brain that are involved in speech production and speech perception. Introducing cerebellum control mechanism into the model plays a significant role in improving the mechanism of speech acquisition and production based on DIVA model. The paper studies its learning process, and explores cerebellar contributions to the model, that is feedforward learning, sensory predictions, feedback command production and the timing of delays, and then constructs a cerebellum model that is closer to neuroanatomy and is applied to DIVA model. Simulation results show that the improved DIVA model can produce more clear and explicit speech sounds, and is more close to human-like pronunciation system. The cerebellum model that established in this paper can be applied to speech acquisition and production based on DIVA model. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5388